Chronic patients' satisfaction and priorities regarding medical care, information and services and quality of life: a French online patient community survey - Apolline Adé; Frédérique Debroucker; Laura Delporte; Cécile De Monclin; Emmanuel Fayet; Pierre Legendre; Lise Radoszycki; Michael Chekroun (BMC, 2020)
Abstract Background The French healthcare system is evolving to meet the challenges of an aging population, the growing prevalence of chronic diseases, the development of new technologies and the increasing involvement of patients in the management of their disease. The aim of this study is to assess the satisfaction and priorities of chronic patients regarding medical care, information and services and their quality of life. Methods A cross-sectional study was conducted from February to March 2018 via the French Carenity platform. Adult patients enrolled in type 1 diabetes, heart failure or obesity communities were invited to answer an online questionnaire. A numeric scale from 0 (meaning not satisfied) to 5 was used to evaluate patients' satisfaction. Patients' priorities were assessed using a ranking question. Patients' satisfaction and priorities have been combined in a matrix to identify patients' expectations. Results Sixty-seven respondents of each condition answered a questionnaire. The most important and least satisfactory items about medical care are availability and active listening from healthcare providers, as well as access to coordinated and multidisciplinary care. Regarding information and services, respondents mostly expect connected medical devices, in addition to lifestyle and dietary measures. As for the quality of life, respondents fear that their chronic condition will keep impacting their daily mood and ability to do physical activities. Conclusions This study shows that chronic patients want to be more actively involved in their care pathway. Patient training and therapeutic patient education programs could help them manage their chronic conditions within a patient-centred healthcare system.